2016
DOI: 10.3389/feart.2016.00095
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Drivers of Dissolved Organic Matter Molecular Composition in the Delaware Estuary

Abstract: Estuaries as connectors of freshwater and marine aquatic systems are hotspots of biogeochemical element cycling. In one of the best studied temperate estuaries, the Delaware Estuary (USA), we investigated the variability of dissolved organic matter (DOM) over five sampling cruises along the salinity gradient in August and November of 3 consecutive years. Dissolved organic carbon (DOC) concentrations were more variable in the upper reaches of the estuary (245 ± 49 µmol DOC L −1 ) than at the mouth of the estuar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
83
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 86 publications
11
83
1
Order By: Relevance
“…The correlation coefficient between PC1 and salinity for the pre-incubation samples was −0.87 (p < 0.01). The loading of PC1 ( Figure 1B) shows a pattern typical of river-to-ocean transects (Medeiros et al, 2015c), with high salinity samples enriched with compounds with high H/C ratios compared to lowsalinity samples, which is consistent with the higher abundance of aliphatic structures in marine DOM (Sleighter and Hatcher, 2008;Osterholz et al, 2016). This is also consistent with the strong gradient in DOM sources in the system associated with terrigenous vs. oceanic inputs (Medeiros et al, 2015a).…”
Section: Spatial and Temporal Variations In Dom Compositionsupporting
confidence: 71%
See 2 more Smart Citations
“…The correlation coefficient between PC1 and salinity for the pre-incubation samples was −0.87 (p < 0.01). The loading of PC1 ( Figure 1B) shows a pattern typical of river-to-ocean transects (Medeiros et al, 2015c), with high salinity samples enriched with compounds with high H/C ratios compared to lowsalinity samples, which is consistent with the higher abundance of aliphatic structures in marine DOM (Sleighter and Hatcher, 2008;Osterholz et al, 2016). This is also consistent with the strong gradient in DOM sources in the system associated with terrigenous vs. oceanic inputs (Medeiros et al, 2015a).…”
Section: Spatial and Temporal Variations In Dom Compositionsupporting
confidence: 71%
“…All PCs shown here are significantly different (95% confidence level) from results of PC analysis of spatially and temporally uncorrelated random processes (Overland and Preisendorfer, 1982). The Wilcoxon rank-sum test was used for comparisons between groups of compounds, as in Osterholz et al (2016).…”
Section: Chemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several other studies have shown that the transformation of terrestrial and the new production of autochthonous (marine) DOM compounds leave characteristic molecular imprints (Sleighter and Hatcher, 2008;Kujawinski et al, 2009;Medeiros et al, 2015a,b;Seidel et al, 2015b). Aromatic terrestrial DOM compounds generally decrease along salinity gradients while the DOM heteroatom content increases due to autochthonous production (Sleighter and Hatcher, 2008;Osterholz et al, 2016). Likewise, the alteration of DOM under different redox-regimes can leave identifiable molecular imprints such as the relative enrichment of sulfurcontaining compounds (Schmidt et al, 2009;Seidel et al, 2014Seidel et al, , 2015aSleighter et al, 2014;Gomez-Saez et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, this technique was used to study the transformation of DOM in a wide range of aquatic systems, including terrestrial-to-marine and oxicto-anoxic transition zones (Koch et al, 2005;Kim et al, 2006;Sleighter and Hatcher, 2008;Schmidt et al, 2009;Longnecker and Kujawinski, 2011;Lechtenfeld et al, 2013). For example, in the Delaware Estuary (USA), compositional differences at the molecular level were not reflected in changes of DOC concentrations (Osterholz et al, 2016). Several other studies have shown that the transformation of terrestrial and the new production of autochthonous (marine) DOM compounds leave characteristic molecular imprints (Sleighter and Hatcher, 2008;Kujawinski et al, 2009;Medeiros et al, 2015a,b;Seidel et al, 2015b).…”
Section: Introductionmentioning
confidence: 99%